Fatores influentes sobre atropelamentos de vertebrados silvestres em rodovias da região central do estado do Rio Grande do Sul, Brasil - Santana, Gilson de Souza (2010)
The habitat loss or fragmentation and reduced connectivity among habitats are common aspects in areas with highways.These impacts have close liaison with running over of wild vertebrates. This study aimed to identify and quantify the influencing factors that act directly and indirectly about these accidents. Were monitored four snippets (north, south, east and west) 100 km of highway BR 158, 287, 392 and RST 241, through 48 road route, one week in different snippets each voyage, in the interval December 2008 to December 2009. Examination of the slopes was launched from the town of Santa Maria-RS, at zero km of route, located on the outskirts of the city, and return the same BR occurred after traveling 100 km on the highway. At the end of monitoring, the number of registered animals was 829 individuals belonging to four classes, 43 families, eight orders and 83 species. The percentage of accidents in mammals was 51,63%, in birds 31,97%, reptiles 11,7%, and amphibians 4,7% The sampling effort of 9.600 km traversed resulted in an average of 0,086 roadkill/km. Vertebrates that have suffered most roadkill in class the mammals the opossum (Didelphis albiventris), with 135 records, hog-nosed skunk (Conepatus chinga), with 62, crabeating fox (Cerdocyon thous), 52; in birds eared dove (Zenaida auriculata), with 39 records and rufous hornero (Furnarius rufus), with 39; in reptiles tegu lizards (Tupinambis merianae), with 42 records and in amphibians the cane toad (Rhinella icterica) with 20 animals. Were significant for the occurrence of events variables such as, seasonality, the environment around of the accident, rainfall and temperature in addition to the faunal composition in the four stretches of highways. Were not identified mitigation measures effective on the slopes. It was suggested the installation of safe passage for wildlife across highways, which can minimize the running over in critical areas identified. However, more studies are still needed to identify specific features of the highways and the species present in the region.